India : land policies for growth and poverty reduction (New Delhi, 2007)
In India, land continues to be of enormous economic, social, and symbolic relevance. The way in which access to land can be obtained and its ownership documented is at the core of the livelihood of the large majority of the poor, especially in rural and tribal areas and determines the extent to which increasingly scarce natural resources are managed. Land policies and administration are critical determinants of the transaction cost associated with modalities to access land for business and residential use and, through the ease of using land as collateral for credit, the development of the financial sector. Land also continues to be a major source of government revenue and a key element for implementing government programmes. This implies that land policies and institutions will have a far-reaching impact on the ability to sustain India's current high rate of growth, the extent to which such growth reaches the poor, and the level and spatial distribution of economic activity.
Keywords: Land pollicy-India